Isolation, selection and identification of native species of Trichoderma spp. with biocontrol effect on knot nematodes that affect the cultivation of Asparagus officinalis of the Agroindustrial company Camposol S.A. - Walter Andres Rojas Villacorta (2017)
A total of 26 native strains of Trichoderma were isolated from soil samples growing asparagus (located in the Agroindustrial company Camposol SA, Chao, Peru) and 6 strains were selected based on their growth rate and number of spores, within you strain were identified Trichoderma asperellum, Trichoderma harzianum and Trichoderma atroviride, these presented controlling activity Meloidogyne sp. both in vitro and under greenhouse conditions. These strains were isolated Pope Sucrose Agar (APS) incubated at 25  0.1 ° C for 7 days. In vitro tests were performed on water agar (AA) 1.5%, while in greenhouse tests nine treatments (T) with isolates were performed. Of the nine treatments, there are three control groups, at the T1 was inoculated only Meloidogyne sp. in another T2 it was not inoculated with Meloidogyne sp. and T3 Oxamyl (990ppm) was inoculated. While the other treatments consisted inoculate each strain isolated in their respective seedlings. Following application of the treatments for 45 days the number of root nodules was counted. Prior to the molecular identification of strains with controlling activity Meloidogyne sp. fungal DNA extraction and the amplification was performed by PCR using as a reference the proposed Schlenzig (2009), which he underwent modifications protocol. T. asperelleum TCA 11, T. atroviride TCA 14, T. harzianum TCA 23 colonized eggs of Meloidogyne sp. and tomato plants that were applied with these strains showed fewer root nodules. In conclusion these three strains suggested as potential candidates for industrial production and for use as biological control of Meloidogyne sp.